2022
DOI: 10.1021/acs.est.2c02255
|View full text |Cite
|
Sign up to set email alerts
|

Unique Compensation Effects of Heavy Metals and Phosphorus Copoisoning over NOx Reduction Catalysts

Abstract: Selective catalytic reduction (SCR) of NO x from the flue gas is still a grand challenge due to the easy deactivation of catalysts. The copoisoning mechanisms and multipoisoning-resistant strategies for SCR catalysts in the coexistence of heavy metals and phosphorus are barely explored. Herein, we unexpectedly found unique compensation effects of heavy metals and phosphorus copoisoning over NO x reduction catalysts and the introduction of heavy metals results in a dramatic recovery of NO x reduction activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…For Ti/Ce, Lewis acid sites dominated the surface. CuO modification increased the acid intensity of the catalysts, and there appeared more Brønsted acid sites over TiCu/Ce . As for K-poisoned catalysts in Figure c,d, the NH 3 adsorption behavior on KTi/Ce and KTiCu/Ce catalysts was both inhibited by alkali metals.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For Ti/Ce, Lewis acid sites dominated the surface. CuO modification increased the acid intensity of the catalysts, and there appeared more Brønsted acid sites over TiCu/Ce . As for K-poisoned catalysts in Figure c,d, the NH 3 adsorption behavior on KTi/Ce and KTiCu/Ce catalysts was both inhibited by alkali metals.…”
Section: Resultsmentioning
confidence: 81%
“…CuO modification increased the acid intensity of the catalysts, and there appeared more Brønsted acid sites over TiCu/Ce. 48 As for K-poisoned catalysts in Figure 5c,d, the NH 3 adsorption behavior on KTi/Ce and KTiCu/Ce catalysts was both inhibited by alkali metals. However, it can still be observed that the modification of Cu protected the NH 3 adsorption and more and stabler acid sites were preserved for KTiCu/Ce.…”
Section: Surface Acidic Propertiesmentioning
confidence: 66%
“…Several Py‐IR peaks can be found and the peak located at about 1542 cm −1 is assigned to the C−N stretching of pyridine adsorbed to the Brønsted acid sites [59] . The peaks at about 1445 cm −1 , 1575 cm −1 , 1597 cm −1 , and 1606 cm −1 are attributed to Lewis acid sites [60] . In addition, the peak at about 1490 cm −1 is due to the interaction of pyridine molecules with both Brønsted and Lewis acid sites [61] .…”
Section: Resultsmentioning
confidence: 99%
“…[59] The peaks at about 1445 cm À 1 , 1575 cm À 1 , 1597 cm À 1 , and 1606 cm À 1 are attributed to Lewis acid sites. [60] In addition, the peak at about 1490 cm À 1 is due to the interaction of pyridine molecules with both Brønsted and Lewis acid sites. [61] In order to further explore the influence of thiourea modification and Zr doping on the acid sites of CeO 2 catalyst, the quantitative amounts of Lewis and Brønsted acid sites were calculated according to the Py-IR curves at 150 °C and 300 °C and the results are shown in…”
Section: Py-irmentioning
confidence: 99%
“…Previously, Zhang et al found that the copoisoning of K and phosphorus exhibited a detoxification effect on Fe 2 O 3 /TiO 2 catalysts due to the newly formed Brønsted acid sites provided by phosphate and the enhanced redox ability originated mainly from the Fe–O–P structure. The detoxification effects of heavy metals and phosphorus or SO 2 were also demonstrated on CeO 2 /TiO 2 catalysts. , However, the copoisoning mechanisms for V-based catalysts in the coexistence of arsenic and cadmium are barely explored.…”
Section: Introductionmentioning
confidence: 99%